Environmentally friendly breathable elastic fabric and processing technology thereof

Through the chemical bonding and photoinitiation technology of modified sodium alginate aqueous solution and antibacterial anti-wrinkle agent, combined with cotton fiber blending, the wrinkle and antibacterial properties of bio-based nylon 56 fabrics are solved, and high washing resistance, anti-shrinkage, moisture-absorbing and breathable are obtained. , environmentally friendly, breathable elastic fabric with strong antibacterial effect.

CN118727234BActive Publication Date: 2024-12-17如东鑫利纺织有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229684.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-17
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Bio-based nylon 56 blended fabrics are prone to wrinkles during wear and use. The prior art improves wrinkle resistance by adding chemical additives, and the antibacterial metal particles have poor compatibility with bio-based nylon 56, which affects antibacterial properties.

Method used

Antibacterial fibers are prepared by chemical bonding using modified sodium alginate aqueous solution and antibacterial anti-wrinkle agent, and blended with cotton fibers. Antibacterial properties are improved through photoinitiators and ultraviolet radiation, and environmentally friendly and breathable through specific spinning and weaving processes. Stretch fabric.

Benefits of technology

It has achieved elastic fabrics with high washing resistance, anti-shrinkage, moisture absorption and breathability, and strong antibacterial effects, overcome the problems of single antibacterial effects and easy migration in the existing technology, and improves the overall performance of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 1HWZ4QDANS2WAFMRWGPEWT1LL0MIVX555WEZ0RQA
    Figure 1HWZ4QDANS2WAFMRWGPEWT1LL0MIVX555WEZ0RQA
  • Figure 5GRQKZNGR0B9HQJUIZ4VEV99Y7V6MRGJIEPILVNI
    Figure 5GRQKZNGR0B9HQJUIZ4VEV99Y7V6MRGJIEPILVNI
  • Figure VYCZNVKVH8UQYFJAVXLERXMPVREAOF5KDCDM9ZWL
    Figure VYCZNVKVH8UQYFJAVXLERXMPVREAOF5KDCDM9ZWL
Patent Text Reader

Abstract

The invention relates to an environmentally friendly breathable elastic fabric and a processing technology thereof, belonging to the technical field of textiles, and comprising the following steps: step S1, preparing antibacterial fiber; step S2, preparing antibacterial core-spun yarn; step S3, twisting yarn; and step S4, preparing fabric. The invention adds an antibacterial anti-wrinkle agent to the antibacterial fiber, chemically cross-links the thiol group on the antibacterial anti-wrinkle agent and the double bond on the modified sodium alginate, thereby limiting the displacement of the antibacterial fiber due to shrinkage, and the antibacterial anti-wrinkle agent contains a graphene oxide structure, a pyrimidine ring and a nano zinc oxide structure with good antibacterial performance. In addition, a large number of hydrophilic groups are present on the modified sodium alginate molecular chain in the antibacterial fiber, which can generate hydrogen bonds with the rich oxygen-containing groups in the graphene oxide in the antibacterial anti-wrinkle agent, and through their joint action, the washing resistance, water shrinkage resistance, moisture absorption, air permeability and antibacterial property of the elastic fabric are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textiles, and in particular relates to an environmentally friendly breathable elastic fabric and a processing technology thereof. Background Art

[0002] In recent years, people have been more inclined to a healthy lifestyle, and have been more and more involved in sports. People have higher and higher requirements for the comfort of clothing, such as requiring clothes to have good elasticity and good moisture absorption. Bio-based nylon 56 has the characteristics of good moisture absorption, high elasticity, good wear resistance, light weight and flame retardancy, and is often made into clothing that can be worn next to the body, which has a good market prospect.

[0003] However, bio-based nylon 56 blended fabrics are prone to wrinkling during wearing and use. The prior art often improves its wrinkle resistance by adding chemical additives. This method of treatment will cause the prepared fabric to have a poor feel and reduced wearing performance. In addition, bio-based nylon 56 itself does not have antibacterial properties. In the related art, in order to improve the antibacterial properties of bio-based nylon 56 blended fabrics, it is usually melt-blended with inorganic metal particles with good antibacterial properties in order to achieve the desired effect. Although the above-mentioned modification method can improve the antibacterial properties of bio-based nylon 56 blended fabrics to a certain extent, the compatibility of antibacterial metal particles with bio-based nylon 56 is poor. The mixing of the two phases of antibacterial metal particles and bio-based nylon 56 is achieved only by shearing the screw, which easily leads to insufficient dispersion of antibacterial metal particles in bio-based nylon 56, which is easy to migrate and ultimately affects its antibacterial properties. Based on the above statement, the present application provides an environmentally friendly breathable elastic fabric and its processing technology. Summary of the invention

[0004] In order to produce an elastic fabric with high washing resistance, shrinkage resistance, good moisture absorption and breathability, and strong antibacterial effect, the present application provides an environmentally friendly breathable elastic fabric and a processing technology thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The processing technology of environmentally friendly breathable elastic fabric includes the following steps:

[0007] Step S1, preparing antibacterial fiber: ultrasonically dispersing the antibacterial anti-wrinkle agent in a modified sodium alginate aqueous solution at a mass ratio of 1-3:10:0.02-0.06, heating to 60-70°C, adding a photoinitiator, stirring evenly, irradiating with ultraviolet light for 10-20 minutes to obtain a spinning solution, blending and grinding the spinning solution, standing to degas, and then wet spinning to obtain the antibacterial fiber;

[0008] Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber to obtain blended yarn, using bio-based fiber as inner core yarn and blended yarn as outer core layer, controlling the covering rate to 35-45%, to obtain antibacterial core-spun yarn;

[0009] Step S3, twisting yarn making: twisting the antibacterial core-spun yarn to obtain warp yarn and weft yarn respectively;

[0010] Step S4, preparing fabric: weaving the warp yarn and the weft yarn to obtain an environmentally friendly, breathable and elastic fabric.

[0011] Preferably, in step S1, the photoinitiator is dimethyl benzoate.

[0012] Preferably, the peak wavelength of the irradiation in step S1 is 365nm and the intensity is 80mw / cm 2 .

[0013] Preferably, in step S1, the wet spinning process is specifically that the spinning solution is pressed into the spinning solution by a metering pump, sprayed out through a spinneret, and then subjected to the steps of coagulation bath molding, drawing, washing, drying, and winding.

[0014] Preferably, in step S1, the number of holes in the spinneret is 300-600, and the hole diameter is 0.02-0.4 mm.

[0015] Preferably, the coagulation bath molding includes a first coagulation bath molding, a second coagulation bath molding and a water washing bath, the first coagulation bath is composed of a calcium chloride solution with a mass concentration of 5%, a coagulation bath temperature of 35-45°C, and an immersion time of 20-30min, the second coagulation bath is a calcium chloride solution with a mass concentration of 1%, a coagulation bath temperature of 35-45°C, and an immersion time of 10-20min, and the water washing bath is deionized water, and the water washing temperature is 65-75°C.

[0016] Preferably, in step S2, the draft ratio is 1.5 and the drying temperature is 50-60°C.

[0017] Preferably, in step S2, the blending ratio of the antibacterial fiber and the cotton fiber is 60:40.

[0018] Preferably, in step S2, the bio-based fiber is nylon 56 filament with a special-shaped cross-section of 78dtex / 34f produced by Liaoning Yinzhu Chemical Spinning Group Co., Ltd.

[0019] Preferably, the twist direction of the blended yarn in step S2 is Z, and the twist is 420-460 twists / m.

[0020] Preferably, in step S2, the controlled drawing multiple of the core-spun yarn is 3.2-3.4 times, the twist direction is Z, and the twist is 420-460 twists / m.

[0021] Preferably, in step S3, the core-spun yarn is twisted, the twist direction is controlled to be S, the twist is 700-750 twists / m, and the warp yarn is obtained; the twist direction is controlled to be S, the twist is 380-420 twists / m, and the weft yarn is obtained.

[0022] Preferably, the weaving process parameters in step S4 are: total number of warp roots 8496, upper machine width 210 cm, upper machine warp density 430 roots / 10 cm, upper machine weft density 382 roots / 10 cm, reed number 51, insertion number 2 / reed, finished product width 145 cm, lower machine warp density 408 roots / 10 cm, lower machine weft density 386 roots / 10 cm, warp shrinkage 4%, weft shrinkage 5.8%.

[0023] An environmentally friendly breathable elastic fabric prepared by adopting the processing technology of the environmentally friendly breathable elastic fabric.

[0024] Preferably, the sodium alginate is commercially available from Shandong Jiejing Group Co., Ltd., with a particle size of 800 mesh and a viscosity of 400-500 mPa.

[0025] Preferably, the antibacterial and anti-wrinkle agent is prepared by the following method:

[0026] Step A1, ultrasonically dispersing 2-aminopyrimidine in anhydrous DMF, raising the temperature to 55-65° C. while stirring, then adding triethylamine and toluene, and dripping epichlorohydrin. After the dripping is completed, stirring and reacting for 3-4 hours. After the reaction is completed, filtering, rotary evaporation, dissolving the rotary evaporation product in acetone, filtering, and rotary evaporation of the filtrate to obtain an epoxy monomer, wherein the mass ratio of 2-aminopyrimidine, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 40-60:600-800:3-5:8-16:16-24:10-12. In the above reaction process, with anhydrous DMF as solvent, triethylamine as catalyst, and toluene as dehydrating agent, the amino group on 2-aminopyrimidine and the chlorine atom on epichlorohydrin undergo nucleophilic substitution reaction to obtain an epoxy monomer;

[0027] The structural formula of the epoxy monomer is shown below:

[0028]

[0029] Step A2, ultrasonically dispersing the epoxy monomer and the modified nano zinc oxide in anhydrous DMF, then adding p-toluenesulfonic acid, heating to 110-130°C, stirring for reaction for 3-4h, then centrifuging, washing, and drying to obtain a pyrimidine derivative, wherein the mass ratio of the epoxy monomer, anhydrous DMF, and p-toluenesulfonic acid is 30-40:30:400-600:1-2. In the above reaction process, anhydrous DMF is used as a solvent and p-toluenesulfonic acid is used as a catalyst. The epoxy group on the epoxy monomer undergoes a ring-opening esterification reaction with the hydroxyl group on the modified nano zinc oxide to obtain a pyrimidine derivative;

[0030] Step A3, mixing graphene oxide and deionized water, and ultrasonically dispersing to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8-9, mixing the graphene oxide suspension and the pyrimidine derivative evenly, heating to 75-85° C. under a nitrogen atmosphere, maintaining the speed unchanged, stirring the reaction for 10-20 minutes, filtering, washing, and freeze-drying to constant weight to obtain an antibacterial and anti-wrinkle agent, wherein the mass ratio of the graphene oxide suspension to the pyrimidine derivative is 10:2-4;

[0031] In the above process, the amino group on the pyrimidine derivative first undergoes an amidation reaction with the carboxyl group on the surface of graphene oxide and is grafted onto the surface of graphene oxide, thereby reducing the agglomeration of graphene oxide, improving the dispersion performance of graphene oxide, and enhancing the antibacterial performance of graphene oxide.

[0032] Preferably, in step A3, the concentration of the graphene oxide suspension is 3.3-3.5 g / mL, and the stirring speed is 200-300 rpm.

[0033] Preferably, the modified sodium alginate aqueous solution is prepared by the following method:

[0034] Sodium alginate and deionized water are mixed in a mass ratio of 6-8:100-120:15, stirred evenly at room temperature, the pH value is adjusted to 8-9, and then a mixed solution b of octenyl succinic anhydride and isopropanol is added dropwise, the temperature is kept constant, stirring is continued for 4-6 hours, and the pH value is adjusted to 6.4-6.8, and washed with deionized water until neutral to obtain a modified sodium alginate aqueous solution; wherein, in the mixed solution b, the mass ratio of octenyl succinic anhydride to isopropanol is 1-3:80, and in the above reaction process, deionized water is used as solvent, sodium hydroxide solution is used as alkaline catalyst, sodium alginate and octenyl succinic anhydride undergo ring-opening esterification reaction to obtain a modified sodium alginate solution.

[0035] Preferably, the modified nano zinc oxide is prepared by the following method:

[0036] Step B1, ultrasonically mixing nano zinc oxide, deionized water, anhydrous ethanol and KH-560 for 30-50 minutes, stirring at room temperature for 6-8 hours, centrifuging, washing and drying the precipitate to obtain epoxy zinc oxide, wherein the mass ratio of nano zinc oxide, deionized water, anhydrous ethanol and KH-560 is 5:10:25-35:0.4-0.6;

[0037] Step B2, ultrasonically dispersing epoxy zinc oxide in anhydrous DMF, adding mixed solution a dropwise, raising the temperature to 90-110°C, stirring and reacting for 2-3h, centrifuging after the reaction, washing and drying the precipitate to obtain modified nano zinc oxide, wherein the mass ratio of epoxy zinc oxide, anhydrous DMF and mixed solution a is 5:50-60:15, and the mass ratio of tetrabutylammonium bromide, L-cysteine ​​and anhydrous DMF in the mixed solution a is 1:8-12:70, first treating nano zinc oxide with KH-560 to obtain epoxy zinc oxide, and then under the action of tetrabutylammonium bromide, the carboxyl group of L-cysteine ​​and the epoxy group on the epoxy zinc oxide undergo a ring-opening reaction to obtain modified nano zinc oxide, and in the above reaction process, the amount of L-cysteine ​​is controlled to be higher than that of epoxy zinc oxide, so that after the reaction is completed, there are still remaining carboxyl groups and amino groups that can participate in the subsequent reaction process.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present application adopts antibacterial fiber and cotton fiber obtained by chemically bonding modified sodium alginate aqueous solution and antibacterial wrinkle-proof agent, so that the prepared modified composite fiber has the excellent properties of sodium alginate fiber and cotton cellulose at the same time; the present application adds antibacterial wrinkle-proof agent to the antibacterial fiber, which exerts anti-shrinkage and antibacterial properties on the one hand, and moisture absorption and breathability on the other hand. The anti-shrinkage property is mainly reflected in the chemical cross-linking of the thiol group on the antibacterial wrinkle-proof agent and the double bond on the modified sodium alginate, which limits the displacement of the antibacterial fiber due to shrinkage, thereby achieving anti-shrinkage. Water resistance and antibacterial properties are reflected in three points: one is the antibacterial properties of graphene oxide, the second is the antibacterial properties of pyrimidine rings in pyrimidine derivatives, and the third is the antibacterial properties of nano zinc oxide. Simple technical means are used to achieve multiple antibacterial effects, overcoming the problem that the existing antibacterial agents have a single antibacterial effect and are prone to migration and failure. The moisture absorption and breathability properties are reflected in the fact that there are a large number of hydrophilic groups on the modified sodium alginate molecular chain in the antibacterial fiber, and the graphene oxide in the antibacterial and anti-wrinkle agent contains rich oxygen-containing groups. Through their joint action, the moisture absorption performance is enhanced. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The processes, conditions, reagents, experimental methods, etc. for implementing the present application, except for those specifically mentioned below, are common knowledge and common common sense in the art and are not particularly limited by the present invention.

[0042] Preparation Examples 1-3 and Comparative Preparation Example 1 provide methods for preparing modified sodium alginate aqueous solutions.

[0043] Preparation Example 1

[0044] The modified sodium alginate aqueous solution is prepared by the following method:

[0045] Sodium alginate and deionized water were mixed in a mass ratio of 6:100:15, stirred at 400 rpm for 30 min at room temperature until uniform, adjusted to pH 8 with 1 M potassium hydroxide solution, and then added dropwise a mixed solution b of octenyl succinic anhydride and isopropanol, and the dripping was controlled to be completed within 30 min. After the dripping was completed, the temperature was kept unchanged and stirring was continued for 4 h. The pH value was then adjusted to 6.4 with 0.6 M hydrochloric acid solution, and washed with deionized water until neutral to obtain a modified sodium alginate aqueous solution, wherein, in the mixed solution b, the mass ratio of octenyl succinic anhydride and isopropanol was 1:80.

[0046] Preparation Example 2

[0047] The modified sodium alginate aqueous solution is prepared by the following method:

[0048] Sodium alginate and deionized water were mixed in a mass ratio of 7:110:15, stirred at 400 rpm for 30 min at room temperature until uniform, adjusted to pH 8.5 with 1 M potassium hydroxide solution, and then added dropwise a mixed solution b of octenyl succinic anhydride and isopropanol, and the dripping was controlled to be completed within 30 min. After the dripping was completed, the temperature was kept constant and stirring was continued for 4 h. The pH value was then adjusted to 6.6 with 0.6 M hydrochloric acid solution, and washed with deionized water until neutral to obtain a modified sodium alginate aqueous solution; wherein, in the mixed solution b, the mass ratio of octenyl succinic anhydride and isopropanol was 2:80.

[0049] Preparation Example 3

[0050] The modified sodium alginate aqueous solution is prepared by the following method:

[0051] Sodium alginate and deionized water were mixed in a mass ratio of 8:120:15, stirred at 400 rpm for 30 min at room temperature until uniform, adjusted to pH 9 with 1 M potassium hydroxide solution, and then added dropwise a mixed solution b of octenyl succinic anhydride and isopropanol, and the dripping was controlled to be completed within 30 min. After the dripping was completed, the temperature was kept constant and stirring was continued for 4 h. The pH value was then adjusted to 6.8 with 0.6 M hydrochloric acid solution, and washed with deionized water until neutral to obtain a modified sodium alginate aqueous solution; wherein, in the mixed solution b, the mass ratio of octenyl succinic anhydride and isopropanol was 2:80.

[0052] Comparative Preparation Example 1

[0053] Sodium alginate and deionized water were mixed in a mass ratio of 6:100:15, stirred at 400 rpm for 30 min at room temperature until uniform, adjusted to pH 8 with 1 M potassium hydroxide solution, and then added dropwise a mixed solution b of 2,2-dimethylsuccinic anhydride and isopropanol, and the dripping was controlled to be completed within 30 min. After the dripping was completed, the temperature was kept unchanged and stirring was continued for 4 h. The pH value was then adjusted to 6.4 with 0.6 M hydrochloric acid solution, and washed with deionized water until neutral to obtain a modified sodium alginate aqueous solution, wherein, in the mixed solution b, the mass ratio of 2,2-dimethylsuccinic anhydride and isopropanol was 1:80.

[0054] Preparation Examples 4-6 and Comparative Preparation Example 2 provide methods for preparing modified nano zinc oxide.

[0055] Preparation Example 4

[0056] Modified nano zinc oxide is prepared by the following method:

[0057] Step B1, nano zinc oxide, deionized water, anhydrous ethanol and KH-560 are mixed in a mass ratio of 5:10:25:0.4, and ultrasonic frequency is 35kHz, ultrasonic power is 500w, ultrasonic frequency is 40min, and stirring is carried out at room temperature and speed is 450rpm for 6h, and centrifugation is performed, and the precipitate is washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 50°C to constant weight to obtain epoxy zinc oxide;

[0058] Step B2, ultrasonically disperse epoxy zinc oxide in anhydrous DMF at a mass ratio of 5:50:15, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 30min, dropwise add mixed solution a, control the dripping to be completed within 30min, after the dripping is completed, heat to 90°C, stir and react at a speed of 600rpm for 2h, after the reaction is completed, centrifuge, wash the precipitate with a mass fraction of 40% ethanol solution for 3 times, and dry at 55°C to constant weight to obtain modified nano zinc oxide, wherein the mixed solution a is prepared by tetrabutylammonium bromide, L-cysteine ​​and anhydrous DMF at a mass ratio of 1:8:70.

[0059] Preparation Example 5

[0060] Modified nano zinc oxide is prepared by the following method:

[0061] Step B1, in a mass ratio of 5:10:30:0.5, nano zinc oxide, deionized water, anhydrous ethanol and KH-560 were ultrasonically treated at an ultrasonic frequency of 35 kHz and an ultrasonic power of 500 W for 40 min, stirred at room temperature for 7 h, centrifuged, washed with anhydrous ethanol and deionized water for 4 times in sequence, and dried at 50° C. to constant weight to obtain epoxy zinc oxide;

[0062] Step B2, ultrasonically disperse epoxy zinc oxide in anhydrous DMF at a mass ratio of 5:55:15, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 30min, add mixed solution a dropwise, control the dripping to be completed within 30min, after the dripping is completed, heat to 100°C, stir and react at a speed of 600rpm for 2.5h, after the reaction is completed, centrifuge, wash the precipitate with a mass fraction of 40% ethanol solution 4 times, and dry at 55°C to constant weight to obtain modified nano zinc oxide, wherein the mixed solution a is prepared by tetrabutylammonium bromide, L-cysteine ​​and anhydrous DMF at a mass ratio of 1:10:70.

[0063] Preparation Example 6

[0064] Modified nano zinc oxide is prepared by the following method:

[0065] Step B1, in a mass ratio of 5:10:35:0.6, nano zinc oxide, deionized water, anhydrous ethanol and KH-560 were ultrasonically treated at an ultrasonic frequency of 35 kHz and an ultrasonic power of 500 W for 40 min, stirred at room temperature for 8 h, centrifuged, and the precipitate was washed with anhydrous ethanol and deionized water for 5 times in sequence, and dried at 50° C. to constant weight to obtain epoxy zinc oxide;

[0066] Step B2, ultrasonically disperse epoxy zinc oxide in anhydrous DMF at a mass ratio of 5:60:15, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 30min, add mixed solution a dropwise, control the dripping to be completed within 30min, after the dripping is completed, heat to 110°C, stir and react at a speed of 600rpm for 3h, after the reaction is completed, centrifuge, wash the precipitate with a mass fraction of 40% ethanol solution 5 times, and dry at 55°C to constant weight to obtain modified nano zinc oxide, wherein the mixed solution a is prepared by tetrabutylammonium bromide, L-cysteine ​​and anhydrous DMF at a mass ratio of 1:12:10.

[0067] Comparative Preparation Example 2

[0068] Modified nano zinc oxide is prepared by the following method:

[0069] Step B1, in a mass ratio of 5:10:25:0.4, nano zinc oxide, deionized water, anhydrous ethanol and KH-560 were ultrasonically treated at an ultrasonic frequency of 35 kHz and an ultrasonic power of 500 W for 40 min, stirred at room temperature and a speed of 450 rpm for 6 h, centrifuged, and the precipitate was washed with anhydrous ethanol and deionized water three times in sequence, and dried at 50° C. to constant weight to obtain epoxy zinc oxide;

[0070] Step B2, disperse epoxy zinc oxide in anhydrous DMF at a mass ratio of 5:50:15, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 30min, add mixed solution a dropwise, control the dripping to be completed within 30min, after the dripping is completed, heat to 90°C, stir and react at a speed of 600rpm for 2h, after the reaction is completed, centrifuge, wash the precipitate with a mass fraction of 40% ethanol solution for 3 times, and dry at 55°C to constant weight to obtain modified nano zinc oxide, wherein the mixed solution a is prepared by tetrabutylammonium bromide, glycine and anhydrous DMF at a mass ratio of 1:8:70.

[0071] Preparation Examples 7-9 and Comparative Preparation Examples 3-4 provide methods for preparing antibacterial anti-wrinkle agents.

[0072] Preparation Example 7

[0073] The antibacterial anti-wrinkle agent is prepared by the following method:

[0074] Step A1, ultrasonically disperse 2-aminopyrimidine in anhydrous DMF at a mass ratio of 40:600:3:8:16:10, control the ultrasonic frequency to 30kHz, the ultrasonic power to 600w, the ultrasonic wave to 40min, and heat to 55°C at a speed of 500rpm while stirring, then add triethylamine and toluene, and drop epichlorohydrin, control the dripping to be completed within 10min, maintain the speed unchanged, and stir to react for 3h. After the reaction is completed, filter, remove anhydrous DMF from the filtrate by rotary evaporation, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, and remove acetone from the filtrate by rotary evaporation to obtain an epoxy monomer;

[0075] Step A2, ultrasonically disperse the epoxy monomer and the modified nano zinc oxide prepared in Preparation Example 4 in anhydrous DMF at a mass ratio of 30:30:400:1, control the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, and the ultrasonic treatment for 35 min, then add p-toluenesulfonic acid, raise the temperature to 110° C., stir and react at a speed of 600 rpm for 3 h, after the reaction is completed, centrifuge, wash with deionized water 3 times, and dry at 55° C. to constant weight to obtain a pyrimidine derivative;

[0076] Step A3, mixing graphene oxide and deionized water, ultrasonically dispersing to obtain a graphene oxide suspension with a concentration of 3.3 g / mL, adjusting the pH value to 8 with 1M sodium hydroxide solution at room temperature, stirring the graphene oxide suspension and the pyrimidine derivative at a mass ratio of 10:2 and a rotation speed of 200 rpm for 35 minutes until uniform, heating to 75°C under a nitrogen atmosphere, maintaining the rotation speed unchanged, stirring and reacting for 15 minutes, filtering after the reaction, washing with deionized water 3 times, and freeze-drying to constant weight to obtain an antibacterial and anti-wrinkle agent.

[0077] Preparation Example 8

[0078] The antibacterial anti-wrinkle agent is prepared by the following method:

[0079] Step A1, ultrasonically disperse 2-aminopyrimidine in anhydrous DMF at a mass ratio of 50:700:4:12:20:11, control the ultrasonic frequency to 30kHz, the ultrasonic power to 600w, the ultrasonication to 40min, the rotation speed to 500rpm, stir and heat to 60°C, then add triethylamine and toluene, add epichlorohydrin dropwise, control the dripping to be completed within 10min, maintain the speed unchanged, continue stirring and reacting for 3.5h, filter after the reaction, remove anhydrous DMF from the filtrate by rotary evaporation, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, and remove acetone from the filtrate by rotary evaporation to obtain an epoxy monomer;

[0080] Step A2, ultrasonically disperse the epoxy monomer and the modified nano zinc oxide prepared in Preparation Example 5 in anhydrous DMF at a mass ratio of 35:30:500:1.5, control the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, and the ultrasonic treatment for 35 min, then add p-toluenesulfonic acid, raise the temperature to 120° C., stir and react at a speed of 600 rpm for 3.5 h, after the reaction is completed, centrifuge, wash with deionized water 4 times, and dry at 60° C. to constant weight to obtain a pyrimidine derivative;

[0081] Step A3, mixing graphene oxide and deionized water, ultrasonically dispersing to obtain a graphene oxide suspension with a concentration of 3.4 g / mL, adjusting the pH value to 8.5 with 1M sodium hydroxide solution at room temperature, stirring the graphene oxide suspension and the pyrimidine derivative at a mass ratio of 10:3 and a rotation speed of 250 rpm for 35 minutes until uniform, heating to 85°C under a nitrogen atmosphere, maintaining the rotation speed unchanged, stirring and reacting for 15 minutes, filtering after the reaction, washing with deionized water 4 times, and freeze-drying to constant weight to obtain an antibacterial and anti-wrinkle agent.

[0082] Preparation Example 9

[0083] The antibacterial anti-wrinkle agent is prepared by the following method:

[0084] Step A1, ultrasonically disperse 2-aminopyrimidine in anhydrous DMF at a mass ratio of 60:800:5:16:24:12, control the ultrasonic frequency to 30kHz, the ultrasonic power to 600w, the ultrasonication to 40min, the speed to 500rpm, stir and heat to 65°C, then add triethylamine and toluene, add epichlorohydrin dropwise, control the dripping to be completed within 10min, maintain the speed unchanged, continue stirring and reacting for 4h, filter after the reaction, remove anhydrous DMF from the filtrate by rotary evaporation, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, and remove acetone from the filtrate by rotary evaporation to obtain an epoxy monomer;

[0085] Step A2, ultrasonically disperse the epoxy monomer and the modified nano zinc oxide prepared in Preparation Example 6 in anhydrous DMF at a mass ratio of 40:30:600:2, control the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, and the ultrasonic treatment for 35 min, then add p-toluenesulfonic acid, raise the temperature to 13° C., stir and react at a speed of 600 rpm for 4 h, after the reaction is completed, centrifuge, wash with deionized water 5 times, and dry at 65° C. to constant weight to obtain a pyrimidine derivative;

[0086] Step A3, mixing graphene oxide and deionized water, ultrasonically dispersing to obtain a graphene oxide suspension with a concentration of 3.5 g / mL, adjusting the pH value to 9 with 1M sodium hydroxide solution at room temperature, stirring the graphene oxide suspension and the pyrimidine derivative at a mass ratio of 10:4 and a rotation speed of 300 rpm for 35 minutes until uniform, heating to 85°C under a nitrogen atmosphere, maintaining the rotation speed unchanged, stirring and reacting for 20 minutes, filtering after the reaction, washing with deionized water 5 times, and freeze-drying to constant weight to obtain an antibacterial and anti-wrinkle agent.

[0087] Comparative Preparation Example 3

[0088] The antibacterial anti-wrinkle agent is prepared by the following method:

[0089] Step A1, ultrasonically disperse 2-aminopyrimidine in anhydrous DMF at a mass ratio of 40:600:3:8:16:10, control the ultrasonic frequency to 30kHz, the ultrasonic power to 600w, the ultrasonic wave to 40min, and the speed to 500rpm while stirring and heating to 55°C, then add triethylamine and toluene, and drop epichlorohydrin, and control the dripping to be completed within 10min. After the dripping is completed, maintain the speed unchanged, continue stirring and reacting for 3h. After the reaction is completed, filter, remove anhydrous DMF from the filtrate by rotary evaporation, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, and remove acetone from the filtrate by rotary evaporation to obtain an epoxy monomer;

[0090] Step A2, ultrasonically disperse the epoxy monomer and the modified nano zinc oxide prepared in Comparative Preparation Example 2 in anhydrous DMF at a mass ratio of 30:30:400:1, control the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, and the ultrasonic treatment for 35 min, then add p-toluenesulfonic acid, raise the temperature to 110° C., stir and react at a speed of 600 rpm for 3 h, after the reaction is completed, centrifuge, wash 3 times, and dry at 55° C. to constant weight to obtain a pyrimidine derivative;

[0091] Step A3, mixing graphene oxide and deionized water, ultrasonically dispersing to obtain a graphene oxide suspension with a concentration of 3.3 g / mL, adjusting the pH value to 8 with 1M sodium hydroxide solution at room temperature, stirring the graphene oxide suspension and the pyrimidine derivative at a mass ratio of 10:2 and a rotation speed of 200 rpm for 35 minutes until uniform, heating to 75°C under a nitrogen atmosphere, maintaining the rotation speed unchanged, stirring and reacting for 15 minutes, filtering after the reaction, washing several times, and freeze-drying to constant weight to obtain an antibacterial and anti-wrinkle agent.

[0092] Comparative Preparation Example 4

[0093] The antibacterial anti-wrinkle agent is prepared by the following method:

[0094] Step A1, ultrasonically disperse pyrimidine-2-carboxylic acid in anhydrous DMF at a mass ratio of 40:600:3:8:16:10, control the ultrasonic frequency to 30kHz, the ultrasonic power to 600w, the ultrasonic wave to 40min, the speed to 500rpm, stir and heat to 55°C, then add triethylamine and toluene, add epichlorohydrin dropwise, control the dripping to be completed within 10min, maintain the speed unchanged, continue stirring and reacting for 3h, filter after the reaction, remove anhydrous DMF from the filtrate by rotary evaporation, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, and remove acetone from the filtrate by rotary evaporation to obtain an epoxy monomer;

[0095] Step A2, ultrasonically disperse the epoxy monomer and the modified nano zinc oxide prepared in Preparation Example 1 in anhydrous DMF at a mass ratio of 30:30:400:1, control the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, and the ultrasonic treatment for 35 min, then add p-toluenesulfonic acid, raise the temperature to 110° C., stir and react at a speed of 600 rpm for 3 h, after the reaction is completed, centrifuge, wash with deionized water 3 times, and dry at 55° C. to constant weight to obtain a pyrimidine derivative;

[0096] Step A3, mixing graphene oxide and deionized water, ultrasonically dispersing to obtain a graphene oxide suspension with a concentration of 3.3 g / mL, adjusting the pH value to 8 with 1M sodium hydroxide solution at room temperature, stirring the graphene oxide suspension and the pyrimidine derivative at a mass ratio of 10:2 and a rotation speed of 200 rpm for 35 minutes until uniform, heating to 75°C under a nitrogen atmosphere, maintaining the rotation speed unchanged, stirring and reacting for 15 minutes, filtering after the reaction, washing with deionized water 3 times, and freeze-drying to constant weight to obtain an antibacterial and anti-wrinkle agent.

[0097] Example 1

[0098] The processing technology of environmentally friendly breathable elastic fabric includes the following steps:

[0099] Step S1, preparing antibacterial fiber: ultrasonically disperse the antibacterial and anti-wrinkle agent prepared in Preparation Example 7 in the modified sodium alginate aqueous solution prepared in Preparation Example 1 at a mass ratio of 1:10:0.02, control the ultrasonic frequency to 35kHz, the ultrasonic power to 500w, ultrasonic for 30min, heat to 60°C, add benzoin dimethyl ether, stir at a speed of 400rpm for 30min until uniform, and then place at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The spinning solution is irradiated under ultraviolet light for 10 minutes to obtain a spinning solution, the spinning solution is blended and ground, and then allowed to stand for degassing, and then the spinning solution is pressed into the spinning solution by a metering pump, and sprayed out through a spinneret with a hole number of 300 and a hole diameter of 0.02 mm, and then subjected to coagulation bath molding, drafting, water washing, drying, and winding to obtain an antibacterial fiber, wherein the coagulation bath molding includes a first coagulation bath molding, a second coagulation bath molding, and a water washing bath, the first coagulation bath composition is a calcium chloride solution with a mass concentration of 5%, the coagulation bath temperature is 35°C, and the immersion time is 20 minutes, the second coagulation bath is a calcium chloride solution with a mass concentration of 1%, the coagulation bath temperature is 35°C, the immersion time is 10 minutes, the water washing bath is deionized water, the water washing temperature is 65°C, the draft ratio is 1.5, and the drying temperature is 50°C;

[0100] Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber at a blending ratio of 60:40 to obtain blended yarn, using nylon 56 filament as inner core yarn and blended yarn as outer core layer, and controlling the covering rate to 35%, to obtain antibacterial core-spun yarn;

[0101] Step S3, twisting yarn making: twisting the antibacterial core-spun yarn, controlling the twist direction to be S and the twist degree to be 700 twists / m, to obtain the warp yarn, and controlling the twist direction to be S and the twist degree to be 380 twists / m, to obtain the weft yarn;

[0102] Step S4, preparing fabric: using 2 / 1 twill weave, weaving warp yarn and weft yarn to obtain environmentally friendly breathable elastic fabric, controlling the weaving process parameters as follows: total warp number 8496, upper machine width 210 cm, upper machine warp density 430 yarns / 10 cm, upper machine weft density 382 yarns / 10 cm, reed number 51, insertion number 2 / reed, finished product width 145 cm, lower machine warp density 408 yarns / 10 cm, lower machine weft density 386 yarns / 10 cm, warp shrinkage 4%, weft shrinkage 5.8%.

[0103] Example 2

[0104] The processing technology of environmentally friendly breathable elastic fabric includes the following steps:

[0105] Step S1, preparing antibacterial fiber: ultrasonically disperse the antibacterial and anti-wrinkle agent prepared in Preparation Example 8 in the modified sodium alginate aqueous solution prepared in Preparation Example 2 at a mass ratio of 2:10:0.04, control the ultrasonic frequency to 35kHz, the ultrasonic power to 500w, ultrasonic for 30min, raise the temperature to 65°C, add benzoin dimethyl ether, stir at a speed of 400rpm for 30min, and then place at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The spinning solution is irradiated under ultraviolet light for 15 minutes to obtain a spinning solution, the spinning solution is blended and ground, and then allowed to stand for degassing, and then the spinning solution is pressed into the spinning solution by a metering pump, and sprayed out through a spinneret with a hole number of 450 and a hole diameter of 0.21 mm, and then subjected to coagulation bath molding, drafting, water washing, drying, and winding to obtain an antibacterial fiber, wherein the coagulation bath molding includes a first coagulation bath molding, a second coagulation bath molding, and a water washing bath, the first coagulation bath composition is a calcium chloride solution with a mass concentration of 5%, the coagulation bath temperature is 40°C, and the immersion time is 25 minutes, the second coagulation bath is a calcium chloride solution with a mass concentration of 1%, the coagulation bath temperature is 40°C, the immersion time is 15 minutes, the water washing bath is deionized water, the water washing temperature is 70°C, the draft ratio is 1.5, and the drying temperature is 55°C;

[0106] Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber at a blending ratio of 60:40 to obtain blended yarn, using nylon 56 filament as inner core yarn and blended yarn as outer core layer, and controlling the covering rate to 40%, to obtain antibacterial core-spun yarn;

[0107] Step S3, twisting yarn making: after twisting the antibacterial core-spun yarn, the twist direction is controlled to be S, the twist is 725 twists / m, and the warp yarn is obtained; the twist direction is controlled to be S, the twist is 400 twists / m, and the weft yarn is obtained;

[0108] Step S4, preparing fabric: using 2 / 1 twill weave, weaving warp yarn and weft yarn to obtain environmentally friendly breathable elastic fabric, controlling the weaving process parameters as follows: total warp number 8496, upper machine width 210 cm, upper machine warp density 430 yarns / 10 cm, upper machine weft density 382 yarns / 10 cm, reed number 51, insertion number 2 / reed, finished product width 145 cm, lower machine warp density 408 yarns / 10 cm, lower machine weft density 386 yarns / 10 cm, warp shrinkage 4%, weft shrinkage 5.8%.

[0109] Example 3

[0110] The processing technology of environmentally friendly breathable elastic fabric includes the following steps:

[0111] Step S1, preparing antibacterial fiber: ultrasonically disperse the antibacterial anti-wrinkle agent prepared in Preparation Example 9 in the modified sodium alginate aqueous solution prepared in Preparation Example 3 at a mass ratio of 3:10:0.06, control the ultrasonic frequency to 35kHz, the ultrasonic power to 500w, ultrasonic for 30min, heat to 70°C, add benzoin dimethyl ether, stir at 400rpm for 30min until uniform, and then place at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The spinning solution is irradiated under ultraviolet light for 20 minutes to obtain a spinning solution, the spinning solution is blended and ground, and then allowed to stand for degassing, and then the spinning solution is pressed into the spinning solution by a metering pump, and sprayed out through a spinneret with a hole number of 600 and an aperture of 0.4 mm, and then subjected to coagulation bath molding, drafting, water washing, drying, and winding to obtain an antibacterial fiber, wherein the coagulation bath molding includes a first coagulation bath molding, a second coagulation bath molding, and a water washing bath, the first coagulation bath composition is a calcium chloride solution with a mass concentration of 5%, the coagulation bath temperature is 45°C, and the immersion time is 30 minutes, the second coagulation bath is a calcium chloride solution with a mass concentration of 1%, the coagulation bath temperature is 45°C, the immersion time is 20 minutes, the water washing bath is deionized water, the water washing temperature is 75°C, the draft ratio is 1.5, and the drying temperature is 60°C;

[0112] Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber at a blending ratio of 60:40 to obtain blended yarn, using nylon 56 filament as inner core yarn and blended yarn as outer core layer, and controlling the covering rate to 45%, to obtain antibacterial core-spun yarn;

[0113] Step S3, twisting yarn making: twisting the antibacterial core-spun yarn, controlling the twist direction to be S and the twist degree to be 750 twists / m to obtain warp yarn, and controlling the twist direction to be S and the twist degree to be 420 twists / m to obtain weft yarn;

[0114] Step S4, preparing fabric: using 2 / 1 twill weave, weaving warp yarn and weft yarn to obtain environmentally friendly breathable elastic fabric, controlling the weaving process parameters as follows: total warp number 8496, upper machine width 210 cm, upper machine warp density 430 yarns / 10 cm, upper machine weft density 382 yarns / 10 cm, reed number 51, insertion number 2 / reed, finished product width 145 cm, lower machine warp density 408 yarns / 10 cm, lower machine weft density 386 yarns / 10 cm, warp shrinkage 4%, weft shrinkage 5.8%.

[0115] In order to verify the comprehensive performance of the environmentally friendly breathable elastic fabrics produced in Examples 1-3 of the present application, the present application sets up Comparative Examples 1-3.

[0116] Comparative Example 1

[0117] The processing technology of environmentally friendly breathable elastic fabric includes the following steps:

[0118] Step S1, preparing antibacterial fiber: ultrasonically disperse the antibacterial anti-wrinkle agent prepared in Preparation Example 7 in the modified sodium alginate aqueous solution prepared in Comparative Preparation Example 1 at a mass ratio of 1:10:0.02, control the ultrasonic frequency to 35kHz, the ultrasonic power to 500w, ultrasonic for 30min, heat to 60°C, add benzoin dimethyl ether, stir at a speed of 400rpm for 30min until uniform, and then place at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The spinning solution is irradiated under ultraviolet light for 10 minutes to obtain a spinning solution, the spinning solution is blended and ground, and then allowed to stand for degassing, and then the spinning solution is pressed into the spinning solution by a metering pump, and sprayed out through a spinneret with a hole number of 300 and a hole diameter of 0.02 mm, and then subjected to coagulation bath molding, drafting, water washing, drying, and winding to obtain an antibacterial fiber, wherein the coagulation bath molding includes a first coagulation bath molding, a second coagulation bath molding, and a water washing bath, the first coagulation bath composition is a calcium chloride solution with a mass concentration of 5%, the coagulation bath temperature is 35°C, and the immersion time is 20 minutes, the second coagulation bath is a calcium chloride solution with a mass concentration of 1%, the coagulation bath temperature is 35°C, the immersion time is 10 minutes, the water washing bath is deionized water, the water washing temperature is 65°C, the draft ratio is 1.5, and the drying temperature is 50°C;

[0119] Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber at a blending ratio of 60:40 to obtain blended yarn, using nylon 56 filament as inner core yarn and blended yarn as outer core layer, and controlling the covering rate to 35%, to obtain antibacterial core-spun yarn;

[0120] Step S3, twisting yarn making: twisting the antibacterial core-spun yarn, controlling the twist direction to be S and the twist degree to be 700 twists / m, to obtain the warp yarn, and controlling the twist direction to be S and the twist degree to be 380 twists / m, to obtain the weft yarn;

[0121] Step S4, preparing fabric: using 2 / 1 twill weave, weaving warp yarn and weft yarn to obtain environmentally friendly breathable elastic fabric, controlling the weaving process parameters as follows: total warp number 8496, upper machine width 210 cm, upper machine warp density 430 yarns / 10 cm, upper machine weft density 382 yarns / 10 cm, reed number 51, insertion number 2 / reed, finished product width 145 cm, lower machine warp density 408 yarns / 10 cm, lower machine weft density 386 yarns / 10 cm, warp shrinkage 4%, weft shrinkage 5.8%.

[0122] Comparative Example 2

[0123] The processing technology of environmentally friendly breathable elastic fabric includes the following steps:

[0124] Step S1, preparing antibacterial fiber: ultrasonically disperse the antibacterial and anti-wrinkle agent prepared in comparative preparation example 3 in the modified sodium alginate aqueous solution prepared in preparation example 1 at a mass ratio of 1:10:0.02, control the ultrasonic frequency to 35kHz, the ultrasonic power to 500w, ultrasonic for 30min, raise the temperature to 60°C, add benzoin dimethyl ether, stir at a speed of 400rpm for 30min until uniform, and then place at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The spinning solution is irradiated under ultraviolet light for 10 minutes to obtain a spinning solution, the spinning solution is blended and ground, and then allowed to stand for degassing, and then the spinning solution is pressed into the spinning solution by a metering pump, and sprayed out through a spinneret with a hole number of 300 and a hole diameter of 0.02 mm, and then subjected to coagulation bath molding, drafting, water washing, drying, and winding to obtain an antibacterial fiber, wherein the coagulation bath molding includes a first coagulation bath molding, a second coagulation bath molding, and a water washing bath, the first coagulation bath composition is a calcium chloride solution with a mass concentration of 5%, the coagulation bath temperature is 35°C, and the immersion time is 20 minutes, the second coagulation bath is a calcium chloride solution with a mass concentration of 1%, the coagulation bath temperature is 35°C, the immersion time is 10 minutes, the water washing bath is deionized water, the water washing temperature is 65°C, the draft ratio is 1.5, and the drying temperature is 50°C;

[0125] Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber at a blending ratio of 60:40 to obtain blended yarn, using nylon 56 filament as inner core yarn and blended yarn as outer core layer, and controlling the covering rate to 35%, to obtain antibacterial core-spun yarn;

[0126] Step S3, twisting yarn making: twisting the antibacterial core-spun yarn, controlling the twist direction to be S and the twist degree to be 700 twists / m, to obtain the warp yarn, and controlling the twist direction to be S and the twist degree to be 380 twists / m, to obtain the weft yarn;

[0127] Step S4, preparing fabric: using 2 / 1 twill weave, weaving warp yarn and weft yarn to obtain environmentally friendly breathable elastic fabric, controlling the weaving process parameters as follows: total warp number 8496, upper machine width 210 cm, upper machine warp density 430 yarns / 10 cm, upper machine weft density 382 yarns / 10 cm, reed number 51, insertion number 2 / reed, finished product width 145 cm, lower machine warp density 408 yarns / 10 cm, lower machine weft density 386 yarns / 10 cm, warp shrinkage 4%, weft shrinkage 5.8%.

[0128] Comparative Example 3

[0129] The processing technology of environmentally friendly breathable elastic fabric includes the following steps:

[0130] Step S1, preparing antibacterial fiber: ultrasonically disperse the antibacterial and anti-wrinkle agent prepared in Comparative Preparation Example 4 in the modified sodium alginate aqueous solution prepared in Preparation Example 1 at a mass ratio of 1:10:0.02, control the ultrasonic frequency to 35kHz, the ultrasonic power to 500w, ultrasonic for 30min, heat to 60°C, add benzoin dimethyl ether, stir at a speed of 400rpm for 30min until uniform, and then place at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The spinning solution is irradiated under ultraviolet light for 10 minutes to obtain a spinning solution, the spinning solution is blended and ground, and then allowed to stand for degassing, and then the spinning solution is pressed into the spinning solution by a metering pump, and sprayed out through a spinneret with a hole number of 300 and a hole diameter of 0.02 mm, and then subjected to coagulation bath molding, drafting, water washing, drying, and winding to obtain an antibacterial fiber, wherein the coagulation bath molding includes a first coagulation bath molding, a second coagulation bath molding, and a water washing bath, the first coagulation bath composition is a calcium chloride solution with a mass concentration of 5%, the coagulation bath temperature is 35°C, and the immersion time is 20 minutes, the second coagulation bath is a calcium chloride solution with a mass concentration of 1%, the coagulation bath temperature is 35°C, the immersion time is 10 minutes, the water washing bath is deionized water, the water washing temperature is 65°C, the draft ratio is 1.5, and the drying temperature is 50°C;

[0131] Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber at a blending ratio of 60:40 to obtain blended yarn, using nylon 56 filament as inner core yarn and blended yarn as outer core layer, and controlling the covering rate to 35%, to obtain antibacterial core-spun yarn;

[0132] Step S3, twisting yarn making: twisting the antibacterial core-spun yarn, controlling the twist direction to be S and the twist degree to be 700 twists / m, to obtain the warp yarn, and controlling the twist direction to be S and the twist degree to be 380 twists / m, to obtain the weft yarn;

[0133] Step S4, preparing fabric: using 2 / 1 twill weave, weaving warp yarn and weft yarn to obtain environmentally friendly breathable elastic fabric, controlling the weaving process parameters as follows: total warp number 8496, upper machine width 210 cm, upper machine warp density 430 yarns / 10 cm, upper machine weft density 382 yarns / 10 cm, reed number 51, insertion number 2 / reed, finished product width 145 cm, lower machine warp density 408 yarns / 10 cm, lower machine weft density 386 yarns / 10 cm, warp shrinkage 4%, weft shrinkage 5.8%.

[0134] The following performance tests are now performed on the environmentally friendly breathable elastic fabrics prepared in Examples 1-3 and Comparative Examples 1-3:

[0135] 1. Moisture absorption and air permeability test

[0136] Hygroscopicity: Tested according to the national standard GB / T 12704.1-2009 "Test method for moisture permeability of textile fabrics Part 1: Moisture absorption method";

[0137] Air permeability: Tested according to the national standard GB / T 5453-1997 "Determination of air permeability of textile fabrics". The test results are shown in Table 1 below:

[0138] Table 1 Moisture absorption rate and air permeability test results

[0139]

[0140] It can be seen from the data shown in Table 1 above that the environmentally friendly breathable elastic fabrics produced in Examples 1-3 of the present application have excellent moisture absorption and air permeability.

[0141] 2. Elasticity and shrinkage

[0142] Elastic recovery rate: tested according to ASTM D3107-07 (2011) "Standard Test Method for Tensile Properties of Stretch Yarn Woven Fabrics";

[0143] The test was conducted according to the standard AATCC 135 2014 "Dimensional Changes of Fabrics after Home Laundering". The test results are shown in Table 2 below:

[0144] Table 2 Elasticity and shrinkage test results

[0145]

[0146] It can be seen from the data shown in Table 2 above that the environmentally friendly breathable elastic fabrics produced in Examples 1-3 of the present application have high elastic recovery rate, good elasticity, small shrinkage rate and good dimensional stability.

[0147] 3. Antibacterial properties

[0148] Antibacterial rate: According to the national standard GB / T 20944.2-2007 "Evaluation of antibacterial properties of textiles Part 2: Absorption method", the antibacterial performance test was carried out before washing and after 100 washings. The washing method was based on the provisions of GB / T 8629 2001 "Household washing and drying procedures for textile testing". A type B agitator washing machine and washing procedure 8B were selected. The test results are shown in Table 3 below:

[0149] Table 3 Antibacterial rate test results

[0150]

[0151] From the data shown in Table 3 above, it can be seen that after 100 times of washing, the environmentally friendly breathable elastic fabrics produced in Examples 1-3 of the present application can still achieve an antibacterial rate of more than 97% against Staphylococcus aureus and Escherichia coli, which is higher than the national standard evaluation index for antibacterial performance and has excellent antibacterial effect.

[0152] It can be seen from the data shown in Tables 1-3 above that the comprehensive performance of the environmentally friendly breathable elastic fabrics produced in Examples 1-3 of the present application is far better than that of Comparative Examples 1-3.

[0153] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0154] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A processing technology for environmentally friendly breathable elastic fabric, characterized in that: The following steps are involved: Step S1, preparing antibacterial fiber: according to the mass ratio of 1-3: 10:0.02-0.06, ultrasonically disperse the antibacterial and anti-wrinkle agent in the modified sodium alginate aqueous solution, heat to 60-70°C, add a photoinitiator, stir evenly, irradiate with ultraviolet light for 10-20 minutes to obtain a spinning solution, blend and grind the spinning solution, let it stand for degassing, and then obtain the antibacterial fiber by wet spinning; Step S2, preparing antibacterial core-spun yarn: blending antibacterial fiber and cotton fiber to obtain blended yarn, using bio-based fiber as inner core yarn and blended yarn as outer core layer, controlling the covering rate to 35-45%, to obtain antibacterial core-spun yarn; Step S3, twisting yarn making: twisting the antibacterial core-spun yarn to obtain warp yarn and weft yarn respectively; Step S4, preparing fabric: weaving the warp yarn and the weft yarn to obtain an environmentally friendly, breathable and elastic fabric; The antibacterial and anti-wrinkle agent is prepared by combining 2-aminopyrimidine and epichlorohydrin to obtain an epoxy monomer, which is then combined with modified nano zinc oxide to obtain a pyrimidine derivative, and finally combined with graphene oxide. The modified sodium alginate aqueous solution is prepared by the following method: Sodium alginate and deionized water are mixed in a mass ratio of 6-8:100-120:15, stirred evenly at room temperature, the pH value is adjusted to 8-9, and then a mixed solution b of octenyl succinic anhydride and isopropanol is added dropwise, the temperature is kept constant, stirring is continued for 4-6 hours, the pH value is adjusted to 6.4-6.8, and washing is performed to obtain a modified sodium alginate aqueous solution; The modified nano zinc oxide is prepared by the following method: Step B1, mixing nano zinc oxide, deionized water, anhydrous ethanol and KH-560 by ultrasonic for 30-50 min at a mass ratio of 5:10:25-35:0.4-0.6, stirring at room temperature for 6-8 h, centrifuging, washing and drying the precipitate to obtain epoxy zinc oxide; Step B2, ultrasonically dispersing epoxy zinc oxide in anhydrous DMF at a mass ratio of 5:50-60:15, adding the mixed solution a dropwise, heating to 90-110°C, stirring for reaction for 2-3h, centrifuging after the reaction, washing several times, and drying to obtain modified nano zinc oxide; The antibacterial anti-wrinkle agent is prepared by the following method: Step A1, ultrasonically disperse 2-aminopyrimidine in anhydrous DMF at a mass ratio of 40-60:600-800:3-5:8-16:16-24:10-12, raise the temperature to 55-65°C while stirring, add triethylamine and toluene, dropwise add epichlorohydrin, stir and react for 3-4h, filter and rotary evaporate after the reaction, dissolve the rotary evaporated product in acetone, filter, and rotary evaporate the filtrate to obtain an epoxy monomer; Step A2, ultrasonically dispersing epoxy monomer and modified nano zinc oxide in anhydrous DMF at a mass ratio of 30-40:30:400-600:1-2, adding p-toluenesulfonic acid, heating to 110-130° C., stirring for reaction for 3-4 hours, and then centrifuging, washing, and drying to obtain a pyrimidine derivative; Step A3, mixing graphene oxide and deionized water, and ultrasonically dispersing to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8-9, and evenly mixing the graphene oxide suspension and the pyrimidine derivative in a mass ratio of 10:2-4, heating to 75-85° C. under a nitrogen atmosphere, maintaining a constant rotation speed, stirring the reaction for 10-20 minutes, filtering, washing, and freeze-drying to obtain an antibacterial and anti-wrinkle agent.

2. The processing technology of an environmentally friendly breathable elastic fabric according to claim 1 is characterized in that: In the mixed solution a, the mass ratio of tetrabutylammonium bromide, L-cysteine ​​and anhydrous DMF is 1:8-12:

70.

3. The processing technology of an environmentally friendly breathable elastic fabric according to claim 1 is characterized in that: In the mixed solution b, the mass ratio of octenyl succinic anhydride to isopropanol is 1-3:

80.

4. The processing technology of an environmentally friendly breathable elastic fabric according to claim 1 is characterized in that: In the step S2, the wet spinning process specifically comprises the following steps: injecting the spinning solution by a metering pump, spraying the solution through a spinneret, and then going through the steps of coagulation bath forming, drawing, washing, drying, and winding.

5. An environmentally friendly breathable elastic fabric, characterized in that: Obtained by the processing technology of the environmentally friendly breathable elastic fabric according to any one of claims 1 to 4.